The fibonacci numbers in edge coloured unicyclic graphs - Bednarz, Natalia; Włoch, Andrzej; Włoch, Iwona (Utilitas Mathematica, 2018)
In this paper we give the successive lower bounds for the number of all (i4,25)-edge colourings in unicyclic graphs. Moreover we give characterizations of extremal graphs achieving these successive minimum values. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.